At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
multiplying everything by 36 you get; 2x^2+y^2=36 which maybe more clear for you, :)
hey! :) i tried this: x²/16 + y²/36 = 1 (1/16)x² + (1/36)y² = 1 2(1/16)x + 2(1/36)yy' = 0
but so far im not sure what to do after because i know i get x/8 + ?? but then i can't really multiply (1/36) 2y*dy/dx ?
isn't the point here to find dy/dx?
let \(F(x,y)=2x^2+y^2=36\) then: \(dF(x,y)=4xdx+2ydy=0\) from here: \(y'=dy/dx=-4x/2y=-2x/y\)
howd you get this?? let F(x,y)=2x2+y2=36
\(dF(x,y)\) is colled full differential it is: \(dF(x,y)=F_xdx+F_ydy\)
i never seen that before
\(F_x\) is partial derivative respect to x
i know those, but where are the numbers coming from?
in what order, where did you take them?
i know they're given but how did you get 36 on the other side. and 2x^2+y^2let F(x,y)=2x2+y2=36
ok, other way: think that y is actualy a function of x, so it is y=y(x). Then: \(2x^2+y(x)^2=36\) now we differentiate keeping this in mind 4x+2yy'=0 now just solve for y'
yes i know when to differentiate but how did you change the function to that
Ya you right I made a mistake. I was treating 36 like 32, :). Shold be. Rest of steps same. dw:1381788857534:dw|
i know I was going to tell you.
you can't have 36 at the end.
i saw a different way on yahoo, would be be able to help me with this one x²/16 + y²/36 = 1 (1/16)x² + (1/36)y² = 1 2(1/16)x + 2(1/36)yy' = 0 (x/8) + (y/18)y' = 0 (y/18)y' = -(x/8) y' = -(x/8)/(y/18) y' = -(x/8)(18/y) y' = -(9x/4y) y'(2) = -(9(2))/(4(5.2)) y'(2) = -18/20.8 y'(2) = -9/10.4 y'(2) = -0.865
I'm not really sure how they got the 4th step :/.... this part----> + (y/18)*dy/dx ??
2(1/16)x + 2(1/36)yy' = 0 (2/16)x+(2/36)yy'=0 (x/8) + (y/18)y' = 0
yes my question is exactly what you wrote up there .... |dw:1381789520628:dw|(x/8) + (y/18)y' = 0
how did it get simplified to y/18*dy/dx?
your answer is same, just simplify 2 in numerator with 36 in denominator
thanks! :) i dontkknow why i missed that silly stuff.
then i plug in for x and y and find the common denominators rights?
wait we're not done yet! :(
i got -.005379
the question is asking y'(1)
y' = -(9x/4y) so: substitute x=1, y=5.80948 y'(1)=-9/4(5.80948)
okay i got dy/dx=-.387298
got it thanks @myko :))!